Predicting flow conditions over stepped chutes based on ANFIS - Hanbay, Davut; Baylar, Ahmet; Ozpolat, Emrah (Springer, 2009)
Chute flow may be either smooth or stepped. The flow conditions in stepped chutes have been classified into nappe, transition and skimming flows. In this paper, characteristics of flow conditions are presented systematically under a wide range of critical flow depth, step height and chute slope. The Adaptive Network Based Fuzzy Inference System (ANFIS) is used to predict flow conditions in stepped chutes using critical flow depth, step height and chute slope information. The proposed model performance is determined by threefold cross validation method. The evaluated classification accuracy of ANFIS model is 99.01%. The test results showed that the proposed ANFIS model can be used successfully for complex process control in hydraulic systems.
Keywords: ANFIS; Fuzzy membership function; Stepped chute; Flow conditions; Cross validation